Plasma aminothiol oxidation in chronic hemodialysis patients - Himmelfarb, Jonathan; McMenamin, Elizabeth; McMonagle, Ellen (Kidney international, 2002)
Plasma aminothiol oxidation in chronic hemodialysis patients. Plasma aminothiols, including homocysteine, cysteine, and glutathione, function as an important extracellular redox system. We examined the plasma aminothiol concentration and redox status in ten chronic hemodialysis patients compared to ten age-matched healthy subjects. Plasma levels of reduced, free oxidized, and protein-bound homocysteine, cysteine, cysteinylglycine, and glutathione were determined using high-pressure liquid chromatography (HPLC). Total plasma homocysteine, cysteine, and cysteinylglycine levels were significantly elevated in hemodialysis patients before dialysis compared to healthy subjects. Total plasma concentration of cysteine and homocysteine significantly decreased after hemodialysis. The ratio of free oxidized to free reduced homocysteine, cysteine, cysteinylglycine, and glutathione were each significantly elevated before dialysis compared to healthy subjects, and decreased significantly by the end of dialysis. The free oxidized to reduced ratio of cysteine and homocysteine were also significantly correlated with total plasma concentrations. Plasma aminothiols are excessively oxidized in uremia, while the hemodialysis procedure is restorative of redox status. Oxidized aminothiols are candidate uremic toxins.